Humidification Performance of Heat and Moisture Exchangers for Pediatric Use - Yusuke Chikata; Chihiro Sumida; Jun Oto; Hideaki Imanaka; Masaji Nishimura (Critical Care Research and Practice)
Background. While heat and moisture exchangers (HMEs) have been increasingly used for humidification during mechanical ventilation, the efficacy of pediatric HMEs has not yet been fully evaluated. Methods. We tested ten pediatric HMEs when mechanically ventilating a model lung at respiratory rates of 20 and 30 breaths/min and pressure control of 10, 15, and 20 cmH2O. The expiratory gas passed through a heated humidifier. We created two rates of leakage: 3.2 L/min (small) and 5.1 L/min (large) when pressure was 10 cmH2O. We measured absolute humidity (AH) at the Y-piece. Results. Without leakage, eight of ten HMEs maintained AH at more than 30 mg/L. With the small leak, AH decreased below 30 mg/L (26.6 to 29.5 mg/L), decreasing further (19.7 to 27.3 mg/L) with the large leak. Respiratory rate and pressure control level did not affect AH values. Conclusions. Pediatric HMEs provide adequate humidification performance when leakage is absent.